Direct Synthesis of Organic Azides from Alcohols Using 2-Azido-1,3-dimethylimidazolinium Hexafluorophosphate - Kitamura, Mitsuru; Koga, Tatsuya; Yano, Masakazu; Okauchi, Tatsuo (Synlett, 2012)
Direct synthesis of organic azides from alcohols was developed. Azide transfer of 2-azido-1,3-dimethylimidazolinium hexafluorophosphate (ADMP) to alcohols proceeds to give the corresponding azides under mild reaction conditions, which were easily isolated because the byproducts are highly soluble in water.
Keywords: ADMP; azides; diazo compounds; azide transfer; heterocycles